Tuberculosis in Kidney Transplant Recipients: A Nationwide Cohort in a Low Tuberculosis Incidence Country - Feuth Thijs; Rajalahti Iiris; Vasankari Tuula; Gissler Mika; Rimhanen-Finne Ruska; Finne Patrik; Helanterä Ilkka (LIPPINCOTT WILLIAMS & WILKINS, 2025)
Background
World Health Organization recommends tuberculosis (TB) preventive treatment for risk groups such as patients preparing for organ transplantation. Pretransplant screening or treatment of latent TB infection has not been routine practice in Finland.
Methods
In this nationwide registry study, we assessed the risk of TB among kidney transplant recipients compared to the general population. TB cases were identified by data linkage of the national infectious disease and the national transplant registries between 1995 and 2019. Standardized incidence ratios were calculated with adjustment for age, sex, and annual TB dynamics.
Results
A total of 4101 kidney transplants in 3900 recipients with a follow-up of 37 652 patient-years were included. Eighteen TB cases were detected. Patients diagnosed with TB were older (median age 64 y, interquartile range 56-66) at transplantation than those without TB (median 51 y, interquartile range 41-60, P < 0.001). The standardized incidence ratio of TB was 6.9 among kidney transplant recipients compared to general population during the whole study period 1995-2019 but decreased from 12.5 in 1995-2007 to 3.2 in 2008-2019. The standardized incidence ratio was 44.2 during the first year after transplantation. Significant differences in 5-y graft losses were not detected between TB patients and those without TB.
Conclusions
The standardized incidence ratio of TB in kidney transplant recipients has decreased over the years, but these patients remain at risk of TB, especially during the first posttransplant year. Cost-benefit analysis is required to address feasibility of latent TB infection screening among transplant candidates in countries with low incidence of TB.